PRMT5 promotes progression of endometrioid adenocarcinoma via ERα and cell cycle signaling pathways. (8th January 2021) - Mei, Shuyu; Ge, Shuang; Wang, Jun; Li, Hailing; Jing, Xiaotong; Liang, Ke; Zhang, Xiaoying; Xue, Chaoshuai; Zhang, Cuijuan; Zhang, Tingguo
Abstract: Protein arginine methyltransferase 5 (PRMT5) has previously been reported to be upregulated in many malignant tumors. This study investigated the significance of PRMT5 in endometrial carcinoma (EC) and explored its function in tumorigenesis. Immunohistochemistry was performed to evaluate PRMT5 expression in 62 EC and 66 endometrial hyperplasia samples. The functions of PRMT5 were investigated by cell counting kit‐8, plate colony formation, wound healing, and transwell and flow cytometry assays. Quantitative reverse transcription‐polymerase chain reaction and western blotting were used to measure the expression of PRMT5, changes in estrogen receptor α (ERα), and related functional proteins. Coimmunoprecipitation was performed to examine the interaction of PRMT5 with ERα and its coactivator steroid receptor coactivator‐1 (SRC1). Compared to endometrial hyperplasia tissue, PRMT5 was overexpressed in endometrioid adenocarcinoma (EAC) but not overexpressed in mucinous EC. The main expression pattern of PRMT5 in EAC was cytoplasmic. However, the positive cases of endometrial hyperplasia showed both cytoplasmic and nuclear positivity in the endometrial glands or were mainly positive in stromal cells. Knockdown of PRMT5 significantly inhibited the growth and migration ability of EAC cells and promoted their apoptosis by regulating cyclin D1, c‐myc, p53, and Bcl2 proteins. Furthermore, PRMT5 could form a complex with ERα and SRC1 to promote the expression of ERα. In conclusion, PRMT5 plays a significant role in the progression of EAC by interacting with ERα and impacting the cell cycle signaling pathways.